2022
DOI: 10.1371/journal.pone.0262006
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behaviors among Bangladeshi university students: Prevalence and risk factors

Abstract: Background Bangladeshi university students are considered to be highly suicide-prone compared to other populations and cohorts. However, no prior epidemiological studies have assessed the suicidality (i.e., past-year suicidal ideation [SI], lifetime suicide plan [SP], and lifetime suicide attempt [SA]) among Bangladeshi students, including the variables such as past-year stressful life events and family mental health history. This is arguably a major knowledge gap in the country. Therefore, the present study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…[52] Moreover, mood, anxiety, psychotic, and trauma-related disorders were also significantly associated with suicidal behaviors among Bangladeshi students. [53] During the COVID-19 pandemic, students with psychopathological conditions, including depression, anxiety, and stress, were found to be more likely to have suicidal risk factors,. [20,54] Among demographic features, sex, relationship status, family type, and income were crucial predictors of suicidal risk.…”
Section: Discussionmentioning
confidence: 99%
“…[52] Moreover, mood, anxiety, psychotic, and trauma-related disorders were also significantly associated with suicidal behaviors among Bangladeshi students. [53] During the COVID-19 pandemic, students with psychopathological conditions, including depression, anxiety, and stress, were found to be more likely to have suicidal risk factors,. [20,54] Among demographic features, sex, relationship status, family type, and income were crucial predictors of suicidal risk.…”
Section: Discussionmentioning
confidence: 99%
“…Suicidal attempts were assessed by binary question whether they had ever attempted suicide during the past 12 months. 19 , 20 …”
Section: Methodsmentioning
confidence: 99%
“…Suicidal behaviour such as suicidal ideation is very prominent among university students in Bangladesh. Rasheduzzaman et al (2022) conducted a cross sectional study with university students in Bangladesh. They found that female had higher tendency to commit suicidal behaviour in comparison to male students.…”
Section: Suicidal Behaviour Among University Studentsmentioning
confidence: 99%